2007
DOI: 10.3399/096016407782604848
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of occupational violence and aggression towards GPs: a cross-sectional study

Abstract: Occupational violence and aggression are common in general practice. This study examined occupational violence and aggression against GPs in terms of prevalence and predictive factors, such as sex of GP, and practice location. Over half of the GPs sampled had experienced at least one form of violence and aggression; more female than male GPs experienced sexual harassment; and there was no difference in the number of metropolitan and rural GPs who had experienced violence and aggression. Predictors emerged for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 11 publications
8
47
2
6
Order By: Relevance
“…Some studies investigating bullying arising from patients, colleagues and supervisors among medical doctors during training, residents, emergency physicians, ambulance personnel [17], young doctors and specialists with long career experience exist; including studies conducted in the United States [18][19][20][21], in some European countries [22][23][24][25] as well as in Japan [26]. Harassment and abuse of family physicians in the workplace by patients or colleagues is also an emerging issue in health care environment in Canada [27,28], USA [29], and Australia [30]. Similar studies in the former eastern European countries, after transition from Soviet republics to market economies, are scarce, even though studies on variations of workplace bullying around the globe concluded that the risk of such problems is particularly high in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigating bullying arising from patients, colleagues and supervisors among medical doctors during training, residents, emergency physicians, ambulance personnel [17], young doctors and specialists with long career experience exist; including studies conducted in the United States [18][19][20][21], in some European countries [22][23][24][25] as well as in Japan [26]. Harassment and abuse of family physicians in the workplace by patients or colleagues is also an emerging issue in health care environment in Canada [27,28], USA [29], and Australia [30]. Similar studies in the former eastern European countries, after transition from Soviet republics to market economies, are scarce, even though studies on variations of workplace bullying around the globe concluded that the risk of such problems is particularly high in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5]21,22 As identified previously, 3 female medical clinicians are more vulnerable to experiencing workplace aggression from all sources in Australia than males overall. However, when stratified by doctor type, higher rates of external and internal aggression were detected for female than male specialists only.…”
Section: Discussionmentioning
confidence: 94%
“…5,7,21,24,25 In novel findings, increasing hours worked in the public and NGO sector were weakly associated with external aggression, negatively for males but positively for females, whereas for internal aggression increasing hours worked in private practice for both males and females was weakly protective for aggression exposure. In addition, for male clinicians, having a poor support network of other doctors was positively associated with external aggression, whereas for both male and female clinicians, having a poor support network of other doctors was positively associated with internal aggression.…”
Section: Sex Differences In Aggression In Medical Work Australian Heamentioning
confidence: 89%
See 1 more Smart Citation
“…El estudio de los factores asociados a la VL resulta complejo, puesto que entrelaza diversos aspectos del profesional de salud, del paciente y de los sistemas de salud (7,10,(12)(13)(14) tales como la edad, la especialidad médica y el sexo del médico (7,12) , así como el estado de salud, el sexo del paciente o el efecto de sustancias como el alcohol (7,(12)(13)(14) . No obstante, los aspectos concernientes al sistema de salud han sido poco investigados (7) , más aun en escenarios con sistemas de salud fragmentados como el peruano (15) .…”
Section: Introductionunclassified